Smutgrass Control in Perennial Grass Pastures - Brent Sellers; Neha Rana; José Luiz Carvalho de Souza Dias; Pratap Devkota (EDIS)
This 4-page document provides an overview of smutgrass biology, control, and general recommendations. Written by Brent Sellers, Neha Rana, José Luiz C. S. Dias, and Pratap Devkota, and published by the UF/IFAS Agronomy Department, revised October 2020.